The effects of intra-articular glucocorticoids and exercise on pain and synovitis assessed on static and dynamic magnetic resonance imaging in knee osteoarthritis: exploratory outcomes from a randomized controlled trial. Issue 4 (April 2017) - Riis, R.G.C.; Henriksen, M.; Klokker, L.; Bartholdy, C.; Ellegaard, K.; Bandak, E.; Hansen, B.B.; Bliddal, H.; Boesen, M.
Summary: Objective: The aims of the present knee osteoarthritis (KOA)-study were to: (1) describe and compare the changes in magnetic resonance imaging (MRI)-measures of synovitis following an exercise program preceded by an intra-articular injection of either corticosteroid or isotonic saline and (2) investigate if any of the changes in patient reported outcome measures (PROMs) were associated with changes in MRI-measures of synovitis. Design: We performed a randomized, double-blinded, placebo-controlled clinical trial evaluating the effects of intra-articular corticosteroid vs placebo injections given before exercise therapy in KOA-patients. PROMs were assessed using the KOOS (knee injury and osteoarthritis outcome score). Synovitis was assessed on conventional non-contrast-enhanced, conventional contrast-enhanced (CE) and dynamic contrast-enhanced (DCE) MRI. PROMs and MRIs were obtained prior to the intra-articular injection, after termination of the exercise program (week 14—primary time point) and week 26. Results: Of 100 randomized participants (50 in each allocation group), 91 had complete MRI-data at baseline (63% female, mean age: 62 years, median Kellgren–Lawrence-grade: 3). There were no statistically significant differences between the two interventions in regards of changes in MRI-measures of synovitis at any time-point. At week 14, we found no statistical significant MRI-explanatory variables of either of the PROMs. Conclusions: The present study does not justify the use of intra-articular corticosteroids over intra-articular saline when combined with an exercise program for reduction of synovitis in KOA. The improvement in pain and function following the intervention with intra-articular corticosteroids/saline and exercise could not be explained by a decrease in synovitis on MRI indicating other pain causing/relieving mechanisms in KOA.